(untitled) (Confluenţe Bibliologice, 2025)
The author reﬂects on the edge of the thesis „Indian Inﬂuence over Eminescu’s thinking” written by Amita Bhose, a young woman from India. This work was supported in 1975 under the leadership of PHD, professor Zoe Dumitrescu-Buşulenga. It was issued by publisher house Junimea in 1978 under the title „Eminescu and India” and reprinted by publisher house Cununi de stele in 2010, after 32 years. Mihai Eminescu’s poetry has produced great astonishment upon her. Eminescu cannot be considered only as an European poet, but also Indian, who looks life through the prism of philosophy. Captivated by Eminescu’s creation, she becomes a good expert of literature and Romanian culture They’re surprising of common similarities of Eminescu, Tagore and Calidasa, among which is longing for nature burn all three. About this work, Edgar Papu, great eminoscolog, says that „nowhere in the world the spirit of India is not absorbed” deeper and more appropriate as in Eminescu work.